Patient-reported outcomes in patients with severe maxillary bone atrophy restored with zygomatic implant-supported complete dental prostheses: a systematic review. (4th July 2022) - Sáez-Alcaide, Luis Miguel; Cortés-Bretón-Brinkmann, Jorge; Sánchez-Labrador, Luis; Pérez-González, Fabián; Forteza-López, Alba; Molinero-Mourelle, Pedro; López-Quiles, Juan
Abstract: Introduction and Objective: Zygomatic implants (ZI) offer a good and predictable alternative to reconstructive procedures of atrophic maxillae. The main objetive of this systematic review was to assess the effect of rehabilitation with zygomatic implants on patient's quality of life (QLP) using Patient Reported Outcomes Measures (PROMs). Materials and Methods: This review followed PRISMA guidelines. An automated electronic search was conducted in four databases supplemented by a manual search for relevant articles published until the end of January 2021. The Cochrane Collaboration Risk of Bias tool and the Newcastle-Ottawa Quality Assessment Scale were used to assess the quality of evidence in the studies reviewed. Results: General findings of this systematic review showed substantial increases in Oral health-related quality of life (OHRQoL) among patients restored with ZI and high scores in terms of general satisfaction, especially in chewing ability and esthetics. An overall survival rate of ZI was 98.3% after a mean follow-up time of 46.5 months was observed. Occurrence of 13.1% biological complications and 1.8% technical complications were reported. Conclusions: Patients rehabilitated with zygomatic implant-supported complete dental prostheses showed substantial improvements in OHRQoL and general satisfaction with the treatment received.